2019
DOI: 10.5194/essd-2019-160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Green Edge ice camp campaigns: understanding the processes controlling the under-ice Arctic phytoplankton spring bloom

Abstract: Abstract. The Green Edge initiative was developed to investigate the processes controlling the primary productivity and the fate of organic matter produced during the Arctic phytoplankton spring bloom (PSB) and to determine its role in the ecosystem. Two field campaigns were conducted in 2015 and 2016 at an ice camp located on landfast sea ice southeast of Qikiqtarjuaq Island in Baffin Bay (67.4797N, 63.7895W). During both expeditions, a large suite of physical, chemical and biological variables was measured b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, some genes belonging to eukaryotic translation initiation factors and heat shock proteins are shown to be ultradian in this study, while these genes families have been shown to present conserved harmonic oscillations (ultradian rhythms generated by the circadian clock) between fungi and mammals ( Ananthasubramaniam et al., 2018 ) ( Table S3 ). Here, we propose that ultradian rhythms in C. fimarchicus may be entrained by ambient tidal cues such as potential current reversal, food availability, turbulence, salinity or temperature cycles caused by the tides ( Massicotte et al., 2020 ; Oziel et al., 2019 ; Tessmar-Raible et al., 2011 ). While ultradian oscillations are also observed at the South sea-ice-free station, under-ice currents at North station could lead to important tidal cycles of food availability (from ice algae), salinity or temperature ( Massicotte et al., 2020 ; Oziel et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some genes belonging to eukaryotic translation initiation factors and heat shock proteins are shown to be ultradian in this study, while these genes families have been shown to present conserved harmonic oscillations (ultradian rhythms generated by the circadian clock) between fungi and mammals ( Ananthasubramaniam et al., 2018 ) ( Table S3 ). Here, we propose that ultradian rhythms in C. fimarchicus may be entrained by ambient tidal cues such as potential current reversal, food availability, turbulence, salinity or temperature cycles caused by the tides ( Massicotte et al., 2020 ; Oziel et al., 2019 ; Tessmar-Raible et al., 2011 ). While ultradian oscillations are also observed at the South sea-ice-free station, under-ice currents at North station could lead to important tidal cycles of food availability (from ice algae), salinity or temperature ( Massicotte et al., 2020 ; Oziel et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we propose that ultradian rhythms in C. fimarchicus may be entrained by ambient tidal cues such as potential current reversal, food availability, turbulence, salinity or temperature cycles caused by the tides ( Massicotte et al., 2020 ; Oziel et al., 2019 ; Tessmar-Raible et al., 2011 ). While ultradian oscillations are also observed at the South sea-ice-free station, under-ice currents at North station could lead to important tidal cycles of food availability (from ice algae), salinity or temperature ( Massicotte et al., 2020 ; Oziel et al., 2019 ). Thus, the tidal reorganization at North may facilitate for example ingestion rate ( Conover et al., 1986 ; Ibáñez-Tejero et al., 2018 ; Petrusevich et al., 2020 ; Schmitt et al., 2011 ), as suggested by the increase of ultradian oscillations of key metabolic processes in copepods at this station.…”
Section: Resultsmentioning
confidence: 99%
“…More than 120 different variables were measured dur-154 P. Massicotte et al: The Green Edge ice camp campaigns: an overview Origin of the water ("water", "ice", "melt pond") sample_source Source of the water ("niskin", "underice" "0-1 cm", "0-3 cm", "3-10 cm", "rosette") depth_m Depth at which measurement was made snow_thickness Qualitative value describing the snow cover under which measurement was made ("thin_snow", "thick_snow") mission Mission identifier ("ice_camp_2015", "ice_camp_2016") pi Name(s) of the principal investigator(s) responsible of the measured variable ing the Green Edge landfast-ice expeditions. The complete list of variables is presented in Massicotte et al, 2019a). In the following sections, we present a subset of these variables along with the methods used to collect and measure them.…”
Section: Data Quality Control and Data Processingmentioning
confidence: 99%
“…Because of their pronounced shade adaptation, a brighter future Arctic Ocean could be detrimental to lipid‐rich sympagic (sea‐ice) diatoms, a central link in the bentho‐pelagic food chain (Leu et al 2010). Since the fate of the Arctic Ocean largely depends upon sympagic and planktonic diatom spring bloom responses to climate perturbations, efforts are being deployed to understand determinants of their blooming (Massicotte et al 2020).…”
Section: Figmentioning
confidence: 99%
“…Pennate diatoms dominate the sea‐ice biomass and centric diatoms dominate the phytoplankton ( see Introduction). See (Massicotte et al 2020) for in depth description of the physicochemical parameters determining phytoplankton under‐ice and marginal ice zone (MIZ) spring blooms onset in Baffin Bay. Dashed green line represents the deep chlorophyll maximum (DCM).…”
Section: Figmentioning
confidence: 99%